Increasing severity with unchanged in-hospital mortality in acute hypercapnic respiratory failure (AHRF) at a respiratory ward-based non-invasive ventilation (NIV) unit - Jumaa Bwika,; Shiva Bikmalla,; Hannah Lewis,; Biman Chakraborty,; Norashikin Amran,; Ben Beauchamp,; Joshil Lodhia,; Rahul Mukherjee (European Respiratory Society, 2024)
Introduction: There has been a 462% increase in acute NIV use in COPD (Chandra D et al. AJRCCM 2011) over 11 years in the United States with similar changes in the UK, where this has led to the movement of NIV provision out of critical care. We analyse temporal trends in the severity and outcomes of ward-based NIV practices.